ADMINISTRATION OF DESLORATADINE IN ALLERGIC RHINITIS AND COMORBID ASTHMA IN CHILDREN - E.A. Vishneva; A.A. Alekseeva; A.K. Gevorkyan (Union of pediatricians of Russia, 2008)
Allergic rhinitis is often combined with bronchial asthma and allergic conjunctivitis, favoring the development of another pathology of superior respiratory tract and deteriorating the prognosis. authors demonstrate the common character of pathogenesis of allergic bronchitis and allergic rhinitis, con vincingly explain the necessity of using modern antihistamine medications. The efficiency of second generation of this group drug is shown not only in complete control of allergic rhinitis symptoms but also in the improvement of the course of bronchial asthma, increase in efficiency of bronchial asthma treatment and improvement of children's quality of life.Key words: allergic rhinitis, bronchial asthma, pathogenesis, treatment, quality of life, children.